Penggunaan Abu Terbang PT Indah Kiat Sebagai Bahan Pengisi (Filler) Dalam Campuran Aspal Jenis AC-WC Dengan Pengujian Marshall - Ramadini Febrina; Alfian Malik; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The filler in a concrete asphalt mixture that is commonly used is Portland cement which is relatively expensive. It is expected that the filler is replaced with cheaper materials. Flying ash is a relatively cheaper material because fly ash is waste material. The purpose of this study was to determine the effect of the use of fly ash fillers in ACWC asphalt mixtures. This study used the percentage of optimum asphalt content (KAO), namely 5%, 5.5%, 6%, 6.5% and 7%. The proportion of fly ash used is 0%, 2%, 4%, 6% and 8%. The specifications used follow the 2018 Bina Marga Standard using the Marshall method. The results of this study indicate that the AC-WC mixture using fly ash filler has a better stability value than not using fly ash filler. The recommended level of fly ash for AC-WC mixtures according to specifications is 6% because it has better values of KAO 6,58% stability, flow, VIM, VMA, VFA, and MQ and meets the 2018 Bina Marga standards. Keywords : Fly ash, Filler, AC-WC, Bina Marga Specification 2018